Philippine traditional herbal remedies for hypertension - Parba, Meliza; Demayo, Cesar G. (Intelektual Pustaka Media Utama, 2025)
Certain areas of the Philippines continue to rely on traditional non-pharmacological approaches, such as herbal medicine, for hypertension treatment, a significant public health problem globally. Therefore, a systematic review of plants used in the Philippines to treat hypertension, based on the PRISMA flow diagram, was carried out. Relevant ethnobotanical studies were retrieved from databases such as Google Scholar, ScienceDirect, and PubMed. Following the eligibility screening, 36 ethnobotanical studies were included. The majority of the studies included in this review came from Region XIII (CARAGA), Region VI (Western Visayas), and Region X (Northern Mindanao). The most prevalent plant family and species were Poaceae (12 species) and Cymbopogon citratus (DC.) Stapf. (16 citations), respectively. Leaves were the most common plant parts utilized while decoction was the most frequently mentioned mode of preparation. Oral administration was the most widely used form of administration. This review highlights medicinal plants with potential antihypertensive properties. It underscores the need to conduct a systematic review of their pharmacological properties to determine which have been scientifically validated and are most effective against hypertension.